Quantifying the climate benefits of a virtual versus an in-person format for an international conference - Jacqueline R. Lewy; Casey D. Patnode; Philip J. Landrigan; Joseph C. Kolars; Brent C. Williams (Environmental Health, 2022)
Abstract Background Academic institutions across the globe routinely sponsor large conferences. During the COVID-19 pandemic, many conferences have used all- or partially virtual formats. The conversion of the 2021 Consortium of Universities for Global Health (CUGH) conference, originally planned in-person for Houston, TX USA to an all-virtual format provided an opportunity to quantify the climate-related impacts of in-person versus virtual conferences. Methods From the 2021 CUGH conference registration data, we determined each registrant’s distance from Houston. Using widely available, open-source formulas, we calculated the carbon footprint of each registrant’s round-trip drive or flight had they traveled to Houston. We assumed that registrants traveling more than 300 miles would have flown, with the remainder traveling by automobile. Results Of 1909 registrants, 1447 would have traveled less than 4000 miles, and 389 would have traveled more than 10,000 miles round trip. Total travel-related carbon emissions were estimated at 2436 metric tons of CO2, equivalent to the conservation of 2994 acres of forest for a year. Conclusions Organizations can now readily quantify the climate cost of annual conferences. CUGH’s annual international conference, when held in-person, contributes significantly to carbon emissions. With its focus on promoting global health equity, CUGH may play a lead role in understanding the pros and cons for planetary health of in-person versus virtual conferences. CUGH and other organizations could routinely measure and publish the climate costs of their annual conferences.